Sektor Ekonomi Potensial Sebagai Upaya Peningkatan Produk Domestik Regional Bruto Kabupaten KudusA - Anik Setiyaningrum (Jurnal Administrasi Publik, 2014)
Abstract: Potential Economic Sector For Improving Regional Gross Domestic Product of Kudus Regency. Process of development and economic growth can not run optimally when the development process is not adapted to its potential, so that, it takes the process of identifying potential economic sectors. Kudus can actually gain a greater GDP and increase economic growth if it is able to exploit its potential. The purpose of this study is to analyze the potential economic sectors of Kudus regency. The results of this study show that potential economic sectors based on the Location Quotient and Shift Share analysis are the manufacturing industry and trade, hotel and restaurant. This needs to get the attention of the local government of Â Kudus regency to focus more on the development of Kudus economy superior. Keyword: potential economic sector, location quotient, shift share analysis Abstrak: Sektor Ekonomi Potensial Sebagai Upaya Peningkatan Produk Domestik Regional Bruto Kabupaten Kudus. Proses pembangunan dan pertumbuhan ekonomi tidak dapat berjalan secara maksimal apabila proses pembangunan tidak disesuaikan dengan potensi yang dimilikinya, sehingga dibutuhkan proses identifikasi sektor ekonomi potensial. Kabupaten Kudus sebenarnya dapat meperoleh PDRB yang lebih besar dan meningkatkan pertumbuhan ekonominya jika mampu memanfaatkan potensi yang dimiliki. Tujuan penelitian ini untuk menganalisis sektor ekonomi potensial kabupaten Kudus. Hasil penelitian ini adalah sektor ekonomi potensial berbasis pada analisis Location Quotient dan analisis Shift Share adalah sektor industri pengolahan dan sektor perdagangan, hotel & restoran. Hal ini perlu mendapat perhatian dari pemerintah daerah kabupaten Kudus untuk lebih memfokuskan pengembangan sektor ekonomi unggulannya. Kata kunci: sektor ekonomi potensial, location quotient, analisis shift share